Primary Arthroscopy-Assisted Foveal Repair of Triangular Fibrocartilage Complex Associated with Acute Distal Radius Fractures in Young Adults - Park, Jinsik; Gil, Young-Woon; Lee, Young Seok; Lee, Chang-Hun (Journal of Wrist Surgery, 2024)
Background In distal radius fractures (DRFs) occurring in nonosteoporotic age groups, it is known that triangular fibrocartilage complex (TFCC) injuries are frequently combined, with some experiencing persistent symptomatic instability. However, a gold standard treatment for these associated lesions has not yet been established.Purpose Our purpose was to investigate the outcomes of primary arthroscopy-assisted transosseous foveal repair of the TFCC associated with DRFs in young adults.Materials and Methods Fifteen patients aged <65 years who underwent open reduction and internal fixation for DRF and arthroscopy-assisted repair for foveal tear of the TFCC were included. Those patients were observed to have complete peripheral TFCC tear on preoperative wrist magnetic resonance imaging and intraoperative distal radioulnar joint (DRUJ) stability tests. This was confirmed with an arthroscopic examination. The transosseous technique was used to repair the TFCC after firm fixation of the DRF. The patients were immobilized with the long-arm splint in a neutral position for 2 weeks postoperatively and a removable short-arm splint was applied for another 2 weeks. DRUJ stability, grip strength, and patient-reported outcomes, including disabilities of the arm, shoulder, and hand (DASH) and Patient-Rated Wrist Evaluation scores, were evaluated as primary outcomes at 3, 6, and 12 months postoperatively.Results All patients showed a stable DRUJ throughout the follow-up period. The average grip strength ratio compared to the unaffected side was 69, 83, and 90% at 3, 6, and 12 months after surgery, respectively. The mean DASH score was 26.9, 18.4, and 6.7 at 3, 6, and 12 months postoperatively, respectively.Conclusion Primary arthroscopy-assisted transosseous foveal repair of the TFCC with internal fixation of the distal radius resulted in early recovery and good clinical outcomes in young patients.Level of Evidence Therapeutic, level IV.
Keywords: distal radius fracture; triangular fibrocartilaginous complex tear; distal radioulnar joint instability; wrist arthroscopy; early mobilization